Pain perception in neurodevelopmental animal models of schizophrenia - Franěk, Miloslav; Vaculín, Šimon; Yamamotová, Anna; Šťastný, František; Valešová, Věra; Rokyta, Richard (Physiological research, 2010)
Animal models are important for the investigation of mechanisms and therapeutic approaches in various human diseases, including schizophrenia. Recently, two neurodevelopmental rat models of this psychosis were developed based upon the use of subunit selective N-methyl-D-aspartate receptor agonists – quinolinic acid (QUIN) and N-acetyl-aspartyl-glutamate (NAAG). The aim of this study was to evaluate pain perception in these models. QUIN or NAAG was infused into lateral cerebral ventricles neonatally. In the adulthood, the pain perception was examined. The rats with neonatal brain lesions did not show any significant differences in acute mechanical nociception and in formalin test compared to controls. However, the neonatally lesioned rats exhibited significantly higher pain thresholds in thermal nociception. Increased levels of mechanical hyperalgesia, accompanying the sciatic nerve constriction (neuropathic pain), were also observed in lesioned rats. Although hyperalgesia was more pronounced in QUIN-treated animals, the number of c-Fos-immunoreactive neurons of the lumbar spinal cord was similar in experimental and control rats. We conclude that neonatal brain lesions attenuated the thermal perception in both nociceptive and neuropathic pain whereas mechanical pain was increased in the model of neuropathic pain only. Thus, nociceptive and neuropathic pain belongs – in addition to behavioral changes – among the parameters which are affected in described animal models of schizophrenia.
Keywords: Receptors, N-Methyl-D-Aspartate; modely nemocí na zvířatech; Animals, Newborn; Male; nociceptory; Rats, Wistar; Dipeptides; Physical Stimulation; Schizophrenia; práh bolesti; Neuralgia; měření bolesti; Age Factors; mužské pohlaví; fyzikální stimulace; potkani Wistar; Nociceptors; novorozená zvířata; Injections, Intraventricular; krysa rodu Rattus; Quinolinic Acid; Animals; lidé; ženské pohlaví; Humans; zvířata; Rats; vysoká teplota; schizofrenie; věkové faktory; Disease Models, Animal; injekce intraventrikulární; Financing, Organized; dipeptidy; protoonkogenní proteiny c-fos; Proto-Oncogene Proteins c-fos; kyselina chinolinová; Female; financování organizované; Pain Measurement; Pain Threshold; receptory N-methyl-D-aspartátu; Hot Temperature; neuralgie